A Biologically Inspired Neural Network Model to Gain Insight Into the Mechanisms of Post-Traumatic Stress Disorder and Eye Movement Desensitization and Reprocessing Therapy - Mattera, Andrea; Cavallo, Alessia; Granato, Giovanni; Baldassarre, Gianluca; Pagani, Marco (Frontiers in Psychology, 2022)
Eye movement desensitization and reprocessing (EMDR) therapy is a well established therapeutic method to treat post-traumatic stress disorder (PTSD). However, how EMDR exerts its therapeutic action has been studied in many researches but still needs to be completely understood. This is in part due to a limited knowledge of the neurobiological mechanisms underlying EMDR, and in part to our incomplete understanding of PTSD. In order to model PTSD we used a biologically inspired computational model based on firing rate units, encompassing cortex, hippocampus and amygdala. Through the modulation of its parameters we fitted real data from patients treated with EMDR or classical exposure therapy. This allowed us to gain insights into PTSD mechanisms and to investigate how EMDR achieves trauma remission.